2021
DOI: 10.1002/mp.14855
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of aggressive and indolent prostate cancer on magnetic resonance imaging

Abstract: Purpose While multi‐parametric magnetic resonance imaging (MRI) shows great promise in assisting with prostate cancer diagnosis and localization, subtle differences in appearance between cancer and normal tissue lead to many false positive and false negative interpretations by radiologists. We sought to automatically detect aggressive cancer (Gleason pattern ≥ 4) and indolent cancer (Gleason pattern 3) on a per‐pixel basis on MRI to facilitate the targeting of aggressive cancer during biopsy. Methods We create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 38 publications
0
75
0
Order By: Relevance
“…Castillo et al ( 27 ) systematically reviewed the performance of machine learning applications in PCa classification based on MRI, and found that only one paper (27 publications) compared the performance of radiologists with or without DL model assistance, and presented that evaluation should be performed in a real clinical setting since the ultimate goal of these models is to assist the radiologists in diagnosis. Seetharaman et al ( 28 ) developed a SPCNet model accurately detected aggressive PCa. In our study, we evaluated the DL model in an independent test dataset to assess its clinical application value and to compare it with junior and senior radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Castillo et al ( 27 ) systematically reviewed the performance of machine learning applications in PCa classification based on MRI, and found that only one paper (27 publications) compared the performance of radiologists with or without DL model assistance, and presented that evaluation should be performed in a real clinical setting since the ultimate goal of these models is to assist the radiologists in diagnosis. Seetharaman et al ( 28 ) developed a SPCNet model accurately detected aggressive PCa. In our study, we evaluated the DL model in an independent test dataset to assess its clinical application value and to compare it with junior and senior radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…They improved the accuracy by 20% compared to other methods with similar approaches (accuracy 80.97%). Seetharaman et al [ 99 ] introduced the Stanford Prostate Cancer Network (SPCNet) to learn features specific to each sequence of MRI mapped with histopathology images, achieving a AUC of 0.86–0.89 to detect aggressive cancers and 0.75–0.85 to detect clinically significant lesions.…”
Section: Machine Learning Applications To Enhance Utility Of Prostate...mentioning
confidence: 99%
“…Multiparametric MRI (mpMRI) scans interpreted by expert prostate radiologists provide the best non-invasive diagnosis [15], but is a limited resource that cannot be leveraged freely. Computer-aided diagnosis (CAD) can assist radiologists to diagnose csPCa, but present-day solutions lack standalone performance comparable to that of expert radiologists [16]- [20].…”
Section: Introductionmentioning
confidence: 99%